2020
DOI: 10.1155/2020/6579696
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Proteins Regulate Mitophagy in Lipopolysaccharide-Induced Acute Lung Injury via PINK1/Parkin Signaling Pathway

Abstract: Mitophagy is involved in sepsis-induced acute lung injury (ALI). Bcl-2 family proteins play an important role in mitochondrial homeostasis. However, whether targeting Bcl-2 proteins (Bcl-2 and Bad) could influence mitophagy in ALI remains unclear. In this study, lipopolysaccharide (LPS) was used to induce injury in A549 cells and ALI in mice. LPS treatment resulted in elevated cell apoptosis, enhanced mitophagy, decreased Bcl-2 expression, increased Bad expression, and activation of PINK1/Parkin signaling in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…Overexpression of pro-survival BCL-2 family proteins, and specifically BCL-x L , in cultured cell lines has been shown to inhibit Parkin translocation to the OMM (Hollville et al 2014;Yu et al 2020;Zhang et al 2020). This seems contradictory to the pro-survival role of BCL-x L , as this would decrease the amount of mitophagy, thereby increasing the risk of dysfunctional mitochondria generating ROS.…”
Section: Influence Of Bcl-2 Family Proteins On Parkin Translocationmentioning
confidence: 99%
“…Overexpression of pro-survival BCL-2 family proteins, and specifically BCL-x L , in cultured cell lines has been shown to inhibit Parkin translocation to the OMM (Hollville et al 2014;Yu et al 2020;Zhang et al 2020). This seems contradictory to the pro-survival role of BCL-x L , as this would decrease the amount of mitophagy, thereby increasing the risk of dysfunctional mitochondria generating ROS.…”
Section: Influence Of Bcl-2 Family Proteins On Parkin Translocationmentioning
confidence: 99%
“…However, excessive mitophagy may promote mitochondrial dysfunction and cause cell injury and death [ 37 ]. For example, it has been reported that mitophagy contributes to increased inflammation and lung injury in ALI [ 36 , 38 ]. During ALI, the activation of mitophagy plays a critical role in the production of proinflammatory cytokines including TNF- α , IL-1 β , and IL-6 and these cytokines all play important roles in the progress of ALI [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that Parkin-Pink1-mediated mitophagy contributes to necroptosis and pathology in chronic obstructive pulmonary disease (COPD) [ 37 ]. During ALI, Parkin/Pink1-mediated mitophagy contributes to inflammation [ 36 ]. In consistency with these studies, we discovered that oxyberberine prevented LPS-induced ALI through inhibition of mitophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipopolysaccharide (LPS) is the component of outer cell wall of gram-negative bacteria, which is the main pathogenic substance in sepsis-induced lung injury. And researches have shown that LPS-induced lung epithelial cell injury can be simulated in vivo in sepsis lung injury ( Su et al, 2012 ; Zhang et al, 2020 ). Thus, to determine the protective effect of TP on alveolar epithelium, L2 cells, one kind of alveolar epithelial cell lines, were treated with 100 ng/mL LPS.…”
Section: Discussionmentioning
confidence: 99%